Implementasi Pendekatan 4P Dalam Pembelajaran Pendidikan Islam Kreatif - Sepma Pulthinka Nur Hanip (UIN Mataram, 2020)
This study aims to provide an insight into how the implementation of the 4P approach relies on psychological theory as an effort to develop talent and creativity in Islamic education in order to produce creative students. The focus of the 4P approach is applied in learning in the form of personal, motivational, process, and product as a basic foothold aimed at training and developing talent and creative power. In the perspective of Islamic education, humans are the most perfect creation of Allah. So the teacher is a guide, motivator, and controller in learning and the ultimate goal of Islamic education is our human beings. For this reason, creating a perfect human being must begin by developing his talents and creativity to become creative people using one of the 4P approaches.